A randomised clinical trial of the efficacy of drop squats or leg extension/leg curl exercises to treat clinically diagnosed jumper's knee in athletes: pilot study. Issue 1 (1st February 2001) - Cannell, L J; Taunton, J E; Clement, D B; Smith, C; Khan, K M
Abstract : Objectives —To compare the therapeutic effect of two different exercise protocols in athletes with jumper's knee. Methods —Randomised clinical trial comparing a 12 week programme of either drop squat exercises or leg extension/leg curl exercises. Measurement was performed at baseline and after six and 12 weeks. Primary outcome measures were pain (visual analogue scale 1–10) and return to sport. Secondary outcome measures included quadriceps and hamstring moment of force using a Cybex II isokinetic dynamometer at 30°/second. Differences in pain response between the drop squat and leg extension/curl treatment groups were assessed by 2 (group) × 3 (time) analysis of variance. Two by two contingency tables were used to test differences in rates of return to sport. Analysis of variance (2 (injured versus non-injured leg) × 2 (group) × 3 (time)) was also used to determine differences for secondary outcome measures. Results —Over the 12 week intervention, pain diminished by 2.3 points (36%) in the leg extension/curl group and 3.2 points (57%) in the squat group. There was a significant main effect of both exercise protocols on pain (p<0.01) with no interaction effect. Nine of 10 subjects in the drop squat group returned to sporting activity by 12 weeks, but five of those subjects still had low level pain. Six of nine of the leg extension/curl group returned to sporting activity by 12 weeks and four patients had low level pain. There was no significant difference between groups in numbers returning to sporting activity. There were no differences in the change in quadriceps or hamstring muscle moment of force between groups. Conclusions —Progressive drop squats and leg extension/curl exercises can reduce the pain of jumper's knee in a 12 week period and permit a high proportion of patients to return to sport. Not all patients, however, return to sport by that time.